Traditional (Culinary) Markets as A Tourist Village during The COVID-19 Pandemic and Post-COVID-19 Period: A Socio-Legal Study - Mangunsong, Nurainun; Hanum, Willy Naresta; Kwarteng, Abdul Hamid (UIN Sunan Kalijaga Yogyakarta, 2023)
Village tourism is one of the flagship projects and tourism development priorities of the Yogyakarta Regional Government (DIY Regional Regulation No. 1 of 2019) to optimize the potential of village resources to improve the welfare and economic independence of village communities (Law No. 6 of 2014). To optimize the policy, the DIY Government has developed a management system in the 2015–2025 Regional Tourism Development Master Plan with the facilitation of a Tourism Village Pioneer towards an Independent Tourism Village. The management includes the planning, implementation, and control of tourism village activities. This study will examine the implementation and dynamics of regulations during the COVID-19 pandemic and post-COVID-19. To explain and measure the policy, an empirical (socio-legal) study was conducted on one of the tourist villages,